Implementasi Kebijakan Social Forestry dalam Rangka Pemberdayaan Masyarakat Desa Hutan (Studi pada Pelaksanaan Pengelolaan Hutan Bersama Masyarakat (PHBM) Di Perum Perhutani KPH Parengan) - Sari, Selvana Mia Andan (Jurnal Administrasi Publik, 2014)
Abstract: The Implementation of Social Forestry Policy for the Empowerment of Forest Rural Communities (Study on Implementation of Forest Management with Community (PHBM) by Perum Perhutani KPH Parengan). Deforestation activities by forest rural communities must be closely related to multi-dimension crises including economic, education, culture and morality, it gives unfavorable impact on national forest protection managed by Perum Perhutani KPH Parengan. The communities are lacking of knowledge to distinguish between good and bad behavior, and thus, it gives unfavorable impact on national forest protection managed by Perum Perhutani KPH Parengan. The researcher elevates the social forestry policy for the empowerment of forest rural communities. The researcher used qualitative descriptive methods, in interview with Perum Perhutani KPH Parengan, BKPH Mulyoagung, LMDH Wono Mulyo, and forest rural communities. Result of this research indicates that the implementation of social forestry policy by Perum Perhutani KPH Parengan for the empowerment of forest rural communities is not maximal because of unfavorable social conditions including the low understanding of rural communities about keep the forest preservation. Successful realization of PHBM may need strong commitment from any related parties. The recommendations that can gives are necessary increasing collaboration in forest management activities. Keywords : policy, empowerment of forest rural communities, PHBM Abstrak: Implementasi Kebijakan Social Forestry Dalam Rangka Pemberdayaan Masyarakat Desa Hutan (Studi Pada Pelaksanaan Pengelolaan Hutan Bersama Masyarakat (PHBM) Di Perum Perhutani KPH Parengan). Fenomena deforestasi hutan oleh aktivitas masyarakat desa hutan yang masih dilanda krisis multidimensi yakni krisis ekonomi, pendidikan, budaya dan terutama moral, mengakibatkan dampak bagi perlindungan hutan negara yang dikelola oleh Perum Perhutani KPH Parengan. Peneliti mengangkat kebijakan social forestry dalam rangka pemberdayaan masyarakat desa hutan. Peneliti menggunakan metode kualitatif deskriptif, dengan wawancara mendalam dari Perum Perhutani KPH Parengan, BKPH Mulyoagung, LMDH Wono Mulyo, dan Masyarakat Desa Hutan (MDH). Hasil dari penelitian menunjukkan pelaksanaan Pengelolaan Hutan Bersama Masyarakat (PHBM) belum berjalan secara maksimal dikarenakan keadaan sosial masyarakat desa yang masih rendah pemahaman menjaga kelestarian hutan. Untuk tercapainya PHBM ini diperlukan komitmen yang kuat pada masing-masing pihak yang terkait. Rekomendasi yang dapat diberikan adalah perlu adanya peningkatan kerjasama dalam kegiatan pengelolaan hutan. Â  Kata kunci : kebijakan, pemberdayaan masyarakat desa hutan, PHBM